Perencanaan Desain Single Tuned Passive Filter Harmonisa Pada AC Microgrid Turbin Tenaga Angin - Rhezal Agung Ananto; Rohmanita Duanaputri; Asfari Hariz Santoso; Muhammad Fahmi Hakim (Politeknik Negeri Malang, 2023)
A microgrid usually consists of small-scale of thermal generation sources and other distributed energy resources (DER) such as photovoltaic, wind power, and fuel cells to serve its loads. In this paper microgirid AC system using wind turbines. Microgrid AC systems use an inverter which is a source of harmonics for need to convert to AC system Load . And the system will also get the source of harmonics when the system is connected to the non-linear load. wind turbines can generate harmonics also. So that it can degrade the quality of the power of the system. In addition the power factor, and voltage system is not good. So thesystem mitigate solution is using a passive filter tuned to the affected bus. The simulation results show that the design singgle tune passive filters can be effective and have a good performance in mitigating microgrid system